Local stiffness and work function variations of hexagonal boron nitride on Cu(111) - Grewal, Abhishek; Wang, Yuqi; Münks, Matthias; Kern, Klaus; Ternes, Markus (Beilstein Journal of Nanotechnology, 2021)
Combined scanning tunnelling and atomic force microscopy using a qPlus sensor enables the measurement of electronic and mechanic properties of two-dimensional materials at the nanoscale. In this work, we study hexagonal boron nitride (h-BN), an atomically thin 2D layer, that is van der Waals-coupled to a Cu(111) surface. The system is of interest as a decoupling layer for functional 2D heterostructures due to the preservation of the h-BN bandgap and as a template for atomic and molecular adsorbates owing to its local electronic trapping potential due to the in-plane electric field. We obtain work function (Φ) variations on the h-BN/Cu(111) superstructure of the order of 100 meV using two independent methods, namely the shift of field emission resonances and the contact potential difference measured by Kelvin probe force microscopy. Using 3D force profiles of the same area we determine the relative stiffness of the Moiré region allowing us to analyse both electronic and mechanical properties of the 2D layer simultaneously. We obtain a sheet stiffness of 9.4 ± 0.9 N·m−1, which is one order of magnitude higher than the one obtained for h-BN/Rh(111). Using constant force maps we are able to derive height profiles of h-BN/Cu(111) showing that the system has a corrugation of 0.6 ± 0.2 Å, which helps to demystify the discussion around the flatness of the h-BN/Cu(111) substrate.
Keywords: decoupling layers; hexagonal boron nitride; local stiffness; Moiré superstructure; work function variation

(untitled) - Novoselov, K. S.; Geim, A. K.; Morozov, S. V.; Jiang, D.; Zhang, Y.; Dubonos, S. V.; Grigorieva, I. V.; Firsov, A. A. (Science, 2004)

(untitled) - Novoselov, K. S.; Mishchenko, A.; Carvalho, A.; Castro Neto, A. H. (Science, 2016)

(untitled) - Watanabe, K.; Taniguchi, T.; Kanda, H. (Nat. Mater., 2004)

(untitled) - Dean, C. R.; Young, A. F.; Meric, I.; Lee, C.; Wang, L.; Sorgenfrei, S.; Watanabe, K.; Taniguchi, T.; Kim, P.; Shepard, K. L.; Hone, J. (Nat. Nanotechnol., 2010)

(untitled) - Xue, J.; Sanchez-Yamagishi, J.; Bulmash, D.; Jacquod, P.; Deshpande, A.; Watanabe, K.; Taniguchi, T.; Jarillo-Herrero, P.; LeRoy, B. J. (Nat. Mater., 2011)

(untitled) - Britnell, L.; Gorbachev, R. V.; Jalil, R.; Belle, B. D.; Schedin, F.; Mishchenko, A.; Georgiou, T.; Katsnelson, M. I.; Eaves, L.; Morozov, S. V.; Peres, N. M. R.; Leist, J.; et al. (Science, 2012)

(untitled) - Pakdel, A.; Bando, Y.; Golberg, D. (Chem. Soc. Rev., 2014)

(untitled) - Li, Q.; Zou, X.; Liu, M.; Sun, J.; Gao, Y.; Qi, Y.; Zhou, X.; Yakobson, B. I.; Zhang, Y.; Liu, Z. (Nano Lett., 2015)

(untitled) - Cui, X.; Lee, G.-H.; Kim, Y. D.; Arefe, G.; Huang, P. Y.; Lee, C.-H.; Chenet, D. A.; Zhang, X.; Wang, L.; Ye, F.; Pizzocchero, F.; Jessen, B. S.; et al. (Nat. Nanotechnol., 2015)

(untitled) - Mendelson, N.; Xu, Z.-Q.; Tran, T. T.; Kianinia, M.; Scott, J.; Bradac, C.; Aharonovich, I.; Toth, M. (ACS Nano, 2019)

(untitled) - Bose, S.; García-García, A. M.; Ugeda, M. M.; Urbina, J. D.; Michaelis, C. H.; Brihuega, I.; Kern, K. (Nat. Mater., 2010)

(untitled) - Kahle, S.; Deng, Z.; Malinowski, N.; Tonnoir, C.; Forment-Aliaga, A.; Thontasen, N.; Rinke, G.; Le, D.; Turkowski, V.; Rahman, T. S.; Rauschenbach, S.; Ternes, M.; et al. (Nano Lett., 2012)

(untitled) - Joshi, S.; Bischoff, F.; Koitz, R.; Ecija, D.; Seufert, K.; Seitsonen, A. P.; Hutter, J.; Diller, K.; Urgel, J. I.; Sachdev, H.; Barth, J. V.; Auwärter, W. (ACS Nano, 2014)

(untitled) - Jacobson, P.; Herden, T.; Muenks, M.; Laskin, G.; Brovko, O.; Stepanyuk, V.; Ternes, M.; Kern, K. (Nat. Commun., 2015)

(untitled) - Muenks, M.; Jacobson, P.; Ternes, M.; Kern, K. (Nat. Commun., 2017)

(untitled) - Will, M.; Atodiresei, N.; Caciuc, V.; Valerius, P.; Herbig, C.; Michely, T. (ACS Nano, 2018)

(untitled) - Mehler, A.; Néel, N.; Kröger, J. (J. Phys. Chem. Lett., 2020)

(untitled) - Riss, A.; Richter, M.; Paz, A. P.; Wang, X.-Y.; Raju, R.; He, Y.; Ducke, J.; Corral, E.; Wuttke, M.; Seufert, K.; Garnica, M.; Rubio, A.; et al. (Nat. Commun., 2020)

(untitled) - Nagashima, A.; Tejima, N.; Gamou, Y.; Kawai, T.; Oshima, C. (Phys. Rev. Lett., 1995)

(untitled) - Auwärter, W.; Kreutz, T. J.; Greber, T.; Osterwalder, J. (Surf. Sci., 1999)

(untitled) - Corso, M.; Auwärter, W.; Muntwiler, M.; Tamai, A.; Greber, T.; Osterwalder, J. (Science, 2004)

(untitled) - Berner, S.; Corso, M.; Widmer, R.; Groening, O.; Laskowski, R.; Blaha, P.; Schwarz, K.; Goriachko, A.; Over, H.; Gsell, S.; Schreck, M.; Sachdev, H.; et al. (Angew. Chem., Int. Ed., 2007)

(untitled) - Herden, T.; Ternes, M.; Kern, K. (Nano Lett., 2014)

(untitled) - Schulz, F.; Drost, R.; Hämäläinen, S. K.; Demonchaux, T.; Seitsonen, A. P.; Liljeroth, P. (Phys. Rev. B, 2014)

(untitled) - Laskowski, R.; Blaha, P.; Schwarz, K. (Phys. Rev. B, 2008)

(untitled) - Schwarz, M.; Riss, A.; Garnica, M.; Ducke, J.; Deimel, P. S.; Duncan, D. A.; Thakur, P. K.; Lee, T.-L.; Seitsonen, A. P.; Barth, J. V.; Allegretti, F.; Auwärter, W. (ACS Nano, 2017)

(untitled) - Joshi, S.; Ecija, D.; Koitz, R.; Iannuzzi, M.; Seitsonen, A. P.; Hutter, J.; Sachdev, H.; Vijayaraghavan, S.; Bischoff, F.; Seufert, K.; Barth, J. V.; Auwärter, W. (Nano Lett., 2012)

(untitled) - Siegel, G.; Ciobanu, C. V.; Narayanan, B.; Snure, M.; Badescu, S. C. (Nano Lett., 2017)

(untitled) - Brülke, C.; Heepenstrick, T.; Humberg, N.; Krieger, I.; Sokolowski, M.; Weiß, S.; Tautz, F. S.; Soubatch, S. (J. Phys. Chem. C, 2017)

(untitled) - Zhang, Q.; Yu, J.; Ebert, P.; Zhang, C.; Pan, C.-R.; Chou, M.-Y.; Shih, C.-K.; Zeng, C.; Yuan, S. (ACS Nano, 2018)

Noncontact Atomic Force Microscopy - Baykara, M. Z.; Schwarz, U. D. (3D Force Field Spectroscopy, 2015)

(untitled) - Crommie, M. F.; Lutz, C. P.; Eigler, D. M. (Nature, 1993)

(untitled) - De Renzi, V.; Rousseau, R.; Marchetto, D.; Biagi, R.; Scandolo, S.; del Pennino, U. (Phys. Rev. Lett., 2005)

(untitled) - Ziroff, J.; Gold, P.; Bendounan, A.; Forster, F.; Reinert, F. (Surf. Sci., 2009)

(untitled) - Cassabois, G.; Valvin, P.; Gil, B. (Nat. Photonics, 2016)

Introduction to Solid State Physics - Kittel, C.; McEuen, P. (John Wiley & Sons, 2018)

(untitled) - Wandelt, K. (Appl. Surf. Sci., 1997)

(untitled) - Ploigt, H.-C.; Brun, C.; Pivetta, M.; Patthey, F.; Schneider, W.-D. (Phys. Rev. B, 2007)

(untitled) - Ruffieux, P.; Aït-Mansour, K.; Bendounan, A.; Fasel, R.; Patthey, L.; Gröning, P.; Gröning, O. (Phys. Rev. Lett., 2009)

(untitled) - Borca, B.; Barja, S.; Garnica, M.; Sánchez-Portal, D.; Silkin, V. M.; Chulkov, E. V.; Hermanns, C. F.; Hinarejos, J. J.; Vázquez de Parga, A. L.; Arnau, A.; Echenique, P. M.; Miranda, R. (Phys. Rev. Lett., 2010)

(untitled) - Bokdam, M.; Brocks, G.; Katsnelson, M. I.; Kelly, P. J. (Phys. Rev. B, 2014)

(untitled) - N’Diaye, A. T.; Bleikamp, S.; Feibelman, P. J.; Michely, T. (Phys. Rev. Lett., 2006)

(untitled) - Gundlach, K. H. (Solid-State Electron., 1966)

(untitled) - Melitz, W.; Shen, J.; Kummel, A. C.; Lee, S. (Surf. Sci. Rep., 2011)

(untitled) - Gómez Díaz, J.; Ding, Y.; Koitz, R.; Seitsonen, A. P.; Iannuzzi, M.; Hutter, J. (Theor. Chem. Acc., 2013)

(untitled) - Zerweck, U.; Loppacher, C.; Otto, T.; Grafström, S.; Eng, L. M. (Phys. Rev. B, 2005)

(untitled) - Giessibl, F. J. (Appl. Phys. Lett., 2000)

(untitled) - Ternes, M.; González, C.; Lutz, C. P.; Hapala, P.; Giessibl, F. J.; Jelínek, P.; Heinrich, A. J. (Phys. Rev. Lett., 2011)

(untitled) - Giessibl, F. J.; Hembacher, S.; Herz, M.; Schiller, C.; Mannhart, J. (Nanotechnology, 2004)

Noncontact Atomic Force Microscopy - Morita, S.; Giessibl, F. J.; Meyer, E.; Wiesendanger, R. (Springer International Publishing, 2015)

(untitled) - Nečas, D.; Klapetek, P. (Cent. Eur. J. Phys., 2012)